2019
DOI: 10.1016/j.ijchp.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between childhood abuse and depression in a sample of Chinese people who use methamphetamine

Abstract: Background/Objective Previous studies have shown that childhood abuse is associated with symptoms of depression. This study aims to examine the prevalence of childhood abuse or neglect and its correlation with depression among a sample of Chinese people who use methamphetamine. Method People who use methamphetamine (MA) ( N = 1,173) were recruited from government-operated drug rehabilitation centres in Anhui province, China. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Some have suggested that self-reported psychotic illness is more prevalent among individuals using crystal methamphetamine than among those using other forms of methamphetamine, which may be associated with the purity of crystal methamphetamine and the self-selection of individuals who use this form of the drug. The psychiatric comorbidity of MUD is complex because there is evidence for both preexisting factors that increase the risk for psychiatric disorders (eg, a 44% prevalence of moderate to severe childhood abuse or neglect) . Moreover, early lifetime adversity, such as emotional or sexual trauma, may also increase the likelihood of MUD owing to the fact that some individuals use methamphetamine as a coping method .…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Some have suggested that self-reported psychotic illness is more prevalent among individuals using crystal methamphetamine than among those using other forms of methamphetamine, which may be associated with the purity of crystal methamphetamine and the self-selection of individuals who use this form of the drug. The psychiatric comorbidity of MUD is complex because there is evidence for both preexisting factors that increase the risk for psychiatric disorders (eg, a 44% prevalence of moderate to severe childhood abuse or neglect) . Moreover, early lifetime adversity, such as emotional or sexual trauma, may also increase the likelihood of MUD owing to the fact that some individuals use methamphetamine as a coping method .…”
Section: Clinical Presentationmentioning
confidence: 99%
“…22 Childhood trauma is a primary risk factor for the development of depressive disorders, post-traumatic stress disorder, implicit emotion regulation deficits, and addictive behavior. [23][24][25] LBA in China suffered a lot of psychotic-trauma experiences (e.g, sexual abuse, bullying victimization) that resulted in loneliness, self-harm behaviors, suicidal ideation and depression. [26][27][28][29] Physical neglect in LBA may result in more severe conduct problems, inattention and hyperactivity index than NLBA.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Possible reasons might be the mitigating effect of resilience on the potential long-term effects of ACEs, which may shape the mechanisms of benign resilience, a currently unquanti ed resilience that on the one hand mitigates childhood adversity and on the other hand avoids the emergence of risky behaviors in adulthood thereby reducing the risk of infectious diseases [26,42]. Additionally, we found an association between ACEs and amphetamine-type stimulant abuse, and a study in Anhui Province, China, also showed that 44.6% of methamphetamine users reported negative childhood events [43].…”
Section: Discussionmentioning
confidence: 54%